1989
DOI: 10.1136/bjsm.23.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced knee joint laxity in distance runners.

Abstract: The objectives of this study were to evaluate the effect of exercise on knee joint laxity. If exercise induced laxity is physiological, incorporation of this quality into a ligament replacement material would be indicated. Twenty recreational long distance runners average age 41 (range 24 to 50 yr) were tested before and immediately after 30 minutes of running. Using a computerized goniometer type instrument (Acufex KSS), knee flexion, axial tibial rotation and anterior-posterior tibial displacement were simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…It has been proposed that the extent of joint laxity may be associated with an increased risk to sustain an ACL injury . Several studies have shown that sports activities such as running or a regular workout in volleyball can increase anterior knee laxity . However, only a study performed by Kvist et al has compared TT in females and males after exhausting exercise and found an increase of this parameter in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that the extent of joint laxity may be associated with an increased risk to sustain an ACL injury . Several studies have shown that sports activities such as running or a regular workout in volleyball can increase anterior knee laxity . However, only a study performed by Kvist et al has compared TT in females and males after exhausting exercise and found an increase of this parameter in males.…”
Section: Discussionmentioning
confidence: 99%
“…29 Several studies have shown that sports activities such as running or a regular workout in volleyball can increase anterior knee laxity. 17,20,21,27 However, only a study performed by Kvist et al 21 has compared TT in females and males after exhausting exercise and found an increase of this parameter in males. Nevertheless, these studies measured anterior knee laxity while subjects were relaxed.…”
Section: Discussionmentioning
confidence: 99%
“…15 As such, these increases are thought to result primarily from viscoelastic changes in joint structures rather than muscular fatigue. 15,19 However, as knee laxity continues to increase and remains elevated with increasing exercise duration, 12,15 the potential for higher-risk biomechanics may be compounded as muscular fatigue develops. [20][21][22] We are not aware of any studies in which researchers have examined relationships between concurrent changes in neuromuscular fatigue and knee laxity and lower extremity biomechanics during exercise that are consistent with the duration, intensity, and movement demands of sport activity.…”
mentioning
confidence: 98%
“…ACL injury typically occurs during sports that involve sudden deceleration and change of direction (e.g., soccer, basketball, and football) (8). However, studies examining knee laxity changes during exercise have primarily focused on sagittal plane activities such as flexion/extension isokinetic contractions (24), stationary cycling (1), forward running (9,17,25,36), or a combination thereof (35). While some have incorporated limited cutting and landing activities into their submaximal running protocols (19,25) or examined changes during multidirectional running (6), only two have measured changes after sport practices (e.g., basketball [36] and cheerleading [22]).…”
mentioning
confidence: 99%